PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH MELALUI PENDAFTARAN MEREK JASA DI KECAMATAN GUNUNGPATI SEMARANG SEBAGAI PENINGKATAN IDENTITAS BISNIS DI ERA DIGITAL - Saputra , Rikki Jitu; Jenali, Yosef Suryo Wibowo; Hanafiah, Zahira Nurmahdi; Hasanah, Cantika Aprilia; Protugus, Rafif Nabil; Arrizal, Brian Hafiz; Ramadhan, Resa Piska; Ramadhani, Anggun Tri; Rum, Gresia Wulaning; Nuraini, Rina Waliya; Agusti, Nadila Rama; Mahmuda, Shirly Ampri Alfian; Rinduni, Ridha; Salsabilla, Haniva; Febriyanti, Elvira; Sinawang, Faricha Anggun; Hartanti, Juwita Dwi; fahrurrizkianur, Akhmad (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2025)
Property Rights; Legal economic growth and the quality of life of the community. Micro, Protection. Small, and Medium Enterprises (MSMEs) play an important role in the economy, but many MSME actors are not yet aware of the importance of trademark registration. The socialization activity carried out by Group 2 Class 3 PMM Semarang State University and UPN Veteran Jakarta aims to increase awareness of MSME actors in Gunungpati, Semarang City regarding legal protection through trademark registration. Through education about the benefits and process of trademark registration, participants are expected to understand the importance of Intellectual Property Rights (IPR) and be proactive in protecting their business identity. The results of the socialization showed a significant increase in understanding among participants.